2017
DOI: 10.1021/acscatal.7b00799
|View full text |Cite
|
Sign up to set email alerts
|

Iodine/Visible Light Photocatalysis for Activation of Alkynes for Electrophilic Cyclization Reactions

Abstract: Photocatalytic organic synthesis needs photocatalysts to initiate the reactions and to control the reaction paths. Available photocatalytic systems rely on electron transfer or energy transfer between the photoexcited catalysts and the substrates. We explore a concept based on the photopromoted catalyst coupling to the substrate and the phototriggered catalyst regeneration by elimination from the catalytic cycle. A catalytic amount of elementary I 2 is applied as both a visible light photocatalyst and a π Lewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…One of the first reports featuring molecular iodine as a photocatalyst in combination with molecular oxygen under irradiation of visible light was the activation of alkynes for electrophilic cyclizations by Wang and co‐workers (Scheme , a) . In their report, molecular iodine both acted as a photocatalyst for singlet oxygen generation and as a π‐Lewis acid.…”
Section: Methodsmentioning
confidence: 99%
“…One of the first reports featuring molecular iodine as a photocatalyst in combination with molecular oxygen under irradiation of visible light was the activation of alkynes for electrophilic cyclizations by Wang and co‐workers (Scheme , a) . In their report, molecular iodine both acted as a photocatalyst for singlet oxygen generation and as a π‐Lewis acid.…”
Section: Methodsmentioning
confidence: 99%
“…The Buchwald–Hartwig reaction, Suzuki reaction, and Sonogashira reaction could be successfully implemented by using 2 a as substrate, furnishing the respective products 3 a , 4 a , and 5 a in good‐to‐excellent yields. In addition, 6 a and 7 a could be obtained through the photocatalytic ene reaction and photoreduction of 2 a , respectively. 6 a , featuring an aldehyde group, can be easily transformed into the corresponding alcohol, carboxylic acid, ester, or imidazole .…”
Section: Methodsmentioning
confidence: 99%
“…[6] The ability to absorb visible light (450-600 nm) [7] makes I 2 as uitable photocatalyst in the Mallory reaction, [8] photo-oxidation, [9] aerobic photo-decarboxylation, [10] and other photoreac-tions. [11] In this regard, I 2 has enormous potentiali nm etal-free photocatalysis.…”
mentioning
confidence: 99%
“…Further examination revealed that solvent choice has as ubstantial effect on the observed rate of reaction( Figure 5), underscoring the complexityo fh omogeneous iodine catalysis. [52][53][54] Modeling of solvent molecules within the reaction system wasbeyond the scope of the current work. This includes the potentialf or formation of iodine-solvent or solventmuconate interactions, which may or may not affect catalytic activity.…”
Section: Competing Pathways For Homogeneous Iodine Catalysismentioning
confidence: 99%
“…This includes the potentialf or formation of iodine-solvent or solventmuconate interactions, which may or may not affect catalytic activity. [52][53][54] Modeling of solvent molecules within the reaction system wasbeyond the scope of the current work.…”
Section: Competing Pathways For Homogeneous Iodine Catalysismentioning
confidence: 99%